Film dan Focus Group Discussion: Strategi Promosi Kesehatan untuk Menurunkan Stigma Masyarakat terhadap Orang dengan HIV/AIDS - Sukarno Putri, Paramytha Magdalena; Shaluhiyah, Zahroh; Suryoputro, Antono (Preventia: The Indonesian Journal of Public Health, 2022)
People Living with HIV/AIDS in Demak, Indonesia were still facing social stigma. This research aims to analyze the influence of film and focus group discussions on stigma. A quasi-experimental study with a non-equivalent control group pre-test and post-test design was applied. This research was conducted in two villages, Ngemplik Wetan as the intervention group and Tembok as the control group. The film with focus group discussion was given four times for one month, only to the intervention group. To measure stigma, the Wilcoxon test was used to compare between pre-test and post-test in a group meanwhile the Mann-Whitney test was used to compare between groups. The sample was determined by purposive sampling and used the comparison formula of two sample proportions. The sample of each group is 45 respondents. The results showed that the intervention group have a significant difference in stigma (p is 0.000; Z is -4.716; CI is 95 percent) and the average stigma decreased by 3.65. Whereas the control group did not have a significant difference in stigma (p is 0.200; Z is -0.924; CI is 95 percent) and the average stigma decreased by 0.78. Film and focus group discussions can be used as a health promotion strategy to reduce the social stigma toward ODHA.